Epicurean Stability (eustatheia): A Philosophical Approach of Stress Management - Yapijakis, Christos; Chrousos, George P. (Conatus - Journal of Philosophy, 2022)
Epicurus used an empirical and sensualistic approach to knowledge, creating a consistent, naturalistic, pragmatic and consequentialistic philosophy. The scientific observations of the last centuries have confirmed the basic principles of Epicurean physics, as well the psychotherapeutic approach of Epicurean ethics, which fits human nature. We know from the work “On Frank Criticism” of Epicurean philosopher Philodemus of Gadara, that the teaching methodology of Epicureans included psychoeducational counseling through therapeutic criticism based on friendly freedom of speech and aiming at τῆς ψυχῆς θεραπείαν (psychotherapy) and at knowledge of maintaining mental health and well-being. The Epicureans called εὐστάθεια (eustatheia, “stability”) the psychosomatic balance (τὸ τῆς σαρκὸς καὶ ψυχῆς εὐσταθὲς κατάστημα), which today we call homeostasis (ὁμοιόστασις), and considered it the basis of true happiness. They recognized empirically the stress that disturbed psychosomatic homeostasis as an agitation of the psyche or a painful feeling of the body and used a number of mental and affective techniques (including the tetrapharmakos) to manage stress at its onset, so that it does not evolve into the particularly troublesome conditions of anxiety and/or depression, which may become chronic psychosomatic disorders with significant social consequences. The article discusses the relation of the main ethical teachings of Epicurus with the biological basis of human brain functions and with the management of stress by cognitive and behavioral psychotherapy.